(untitled) (The Pakistan Development Review, 1994)
The National Finance Commission (NFC) award of 1991 has been acclaimed to be a historic achievement of the previous elected government. It has come after a gap of many years (due since 1979) and some abortive attempts earlier.! Meanwhile, the provinces had run into large, chronic deficits on the current account, indicating the growing inadequacy of divisible pool transfers as per the provisions of the 1974 award. Consequently, as an ad hoc provision, deficit grants and other subventions had been used increasingly to support the on-going operations of the provinces. At their peak in 1987-88, these grants were Rs 17 billion (see Table 1), equivalent to about 2 percent of the Gross Domestic Product (GDP) and financed over one-fourths of the provincial current expenditure. Also, the federal government took over the responsibility of provision of some provincial responsibilities as contained in the Concurrent List of the Constitution like SCARPS, flood control, fertiliser subsidy, universities, etc.